A new endangered species of Polygala (Polygalaceae) from Niquêlandia, Goiás, Brazil - Pastore, José Floriano Barêa (Phytotaxa, 2016)
A new endangered species of Polygala restricted to a small area used for nickel mining from Goiás, Brazil is here described. Provided here a description, photos from a dissecting scope, a distribution map, and, additionally, the new species is compared with the morphologically most similar ones, P. appendiculata and P. tenuis.